Analysis on Losses Reduction with Series Capacitor Compensation Application in Distribution Network - Muhammad Azizi bin Mohd Wahidi, Muhammad Azizi (2010)
In this study, series capacitor compensation has been focused in order to find out what is the effect if this type of compensation been installed in distribution network. The element that would be interested for this study will be the losses reduction in the particular network.